A new perspective for advanced positron emission tomography–based molecular imaging in neurodegenerative proteinopathies. Issue 8 (20th June 2019) - Perani, Daniela; Iaccarino, Leonardo; Lammertsma, Adriaan A.; Windhorst, Albert D.; Edison, Paul; Boellaard, Ronald; Hansson, Oskar; Nordberg, Agneta; Jacobs, Andreas H.; ,
Abstract : Recent studies in neurodegenerative conditions have increasingly highlighted that the same neuropathology can trigger different clinical phenotypes or, vice‐versa, that similar phenotypes can be triggered by different neuropathologies. This evidence has called for the adoption of a pathology spectrum‐based approach to study neurodegenerative proteinopathies. These conditions share brain deposition of abnormal protein aggregates, leading to aberrant biochemical, metabolic, functional, and structural changes. Positron emission tomography (PET) is a well‐recognized and unique tool for the in vivo assessment of brain neuropathology, and novel PET techniques are emerging for the study of specific protein species. Today, key applications of PET range from early research and clinical diagnostic tools to their use in clinical trials for both participants screening and outcome evaluation. This position article critically reviews the role of distinct PET molecular tracers for different neurodegenerative proteinopathies, highlighting their strengths, weaknesses, and opportunities, with special emphasis on methodological challenges and future applications.